2021
DOI: 10.1177/15248399211013817
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Adoption of Evidence-Based Health Marketing and Promotion Strategies in Local Communities: Building a Communication Dissemination and Support System for the National Diabetes Prevention Program

Abstract: The Centers for Disease Control and Prevention (CDC) created a health communication marketing and promotion support system (support system) to help 10 CDC-funded national organizations (recipients) grow enrollment of underserved populations in the National Diabetes Prevention Program. This article describes the creation of a successful support system to increase the use of effective marketing approaches and key messaging. The support system was developed using a systematic approach. It included a needs assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others. The article characteristics are summarised in Appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research underwent consisted of fervent discussion concerning how practitioners or a specific population would use digital media to promote good health practices within certain patient groups, i.e., pregnant women, or to prevent the development of conditions such as diabetes and cancer ( Beaudoin and Hong, 2017 ; Collins et al, 2020 ; Williams et al, 2021 ; Álvarez-Pérez et al, 2022 ; John et al, 2022 ). Furthermore, some research has concluded that health promotion should be included as a core lesson in schools to tackle fake news which spread at a speed comparable to a virus replicating in the body.…”
Section: Introductionmentioning
confidence: 99%